PENGARUH VEGETASI TERHADAP TAHANAN ALIRAN PADA SALURAN IRIGASI - I.E. Sulastri Sihotang; Eldina Fatimah; Masimin Masimin (Prodi Magister Teknik Sipil Unsyiah, 2019)
Irrigation channel in D.I. Timbang Deli, Deli Serdang district Sumut province has a total area of 520 Ha and a 5000 meter long secondary channel. Irrigation channel in D.I. Timbang Deli overgrown vegetation at the base and wall of the channel so it is expected to affect roughness. The objective of the study was the flow resistance with the variation of vegetation volume to the variation of the discharge. The method used in this study is field observation by measuring flow velocity, flow depth and vegetation volume (VT) on trapezoidal tract width of 3.75 m and height of 0.90 m along 154 m. Measurements were performed on 3 points of upstream, middle and downstream channels and 5 transverse dots X1 through X5 4 times with D1 debit variation of 1.32 m³/s and D2 of 0.98 m³/s. The dominant vegetation channels are rigid. Measurement velocity using current meter while for vegetation volume (VT) using grid method. The results showed that vegetation volume VT0 (0,00 m³/0,00%), VT1 (52,417 m³/21,14%), VT2 (70,7921 m³/24,51%) and VT3 (83,053 m³/30,42%). It is seen that the increase in vegetation volume can affect the flow resistance. The result of measurement increased the resistance of flow to VT0 0,052, VT1 equal to 0,062 with percentage 16,13%, VT2 equal to 0,108 with percentage 51,85% and VT3 equal to 0,122 with percentage 57,37% atD1. Meanwhile, at D2 there is an increase of flow resistance to VT0 by 0,044, VT1 is 0,052 with percentage 15,38%, VT2 equal to 0,058 with percentage 24,14% and VT3 equal to 0,070 with percentage 37,14%. This shows that the flow resistance VT0 is smaller than the flow resistance VT1, VT2 and VT3. From the above results are expected to conduct O and P channels by surrounding communities and related government.